Vertebrados de la Reserva Biológica Cordillera de Sama, Tarija, Bolivia - Blendinger, Pedro Gerardo (2000)
A survey of the vertebrates of the Reserva Biológica Cordillera de Sama, indicating environmental preference of the species was carried out August 1995. 124 species of vertebrates were record: four species of fish, three of frogs, three of reptiles, 104 of birds and one mammal are recorded for the first time at Tarija Department. The presence of endangered species and four vulnerable species of birds, one of them endemic, and one vulnerable species of mammal are noted. The importance of the protected area for vertebrates conservation is discussed.